Cryopreservation of Boer goat spermatozoa: Comparison of two freezing extenders based on post-thaw sperm quality and fertility rates - Pamungkas, Fitra Aji; Batubara, Aron; ., Anwar (Indonesian Journal of Animal and Veterinary Sciences, 2014)
Boer goat have recently been popularly used for cross breeding with local goats. However, it is currently considered a breed at very limited number with relatively high prices . In this context, the cryopreservation of spermatozoa is important because it could be conserved for a very long period of time. Egg yolk extenders are most commonly used for cryopreservation of goat sperm. The aim of this study was to compare the ability of two extenders to maintain sperm viability after cryopreservation. Semen from three male Boer goat aged about 2-3 years old was collected using artificial vagina and frozen with Tris and Triladyl extender. The results showed that percentage of motility, viability and membrane integrity of spermatozoa with Tris and Triladyl extenders at every stage of cryopreservation showed not significantly difference (P>0.05), except the percentage of sperm motility post thawing of Triladyl was higher than Tris extender (52.00Â±4.47% vs 47.50Â±2.74%, P<0.05). Cryopreserved semen in Tris extender provided the same fertility rates after cervical insemination compared to Triladyl (62.50% vs 60.00%). In conclusion, the Tris extender has the same capabilities to Triladyl in cryopreservation of Boer goat spermatozoa as to maintain sperm quality and fertility rates. Key Words: Boer Goat, Spermatozoa, Cryopreservation, FertilityÂ